Rancang Bangun Aplikasi Penilaian Kinerja Karyawan Menggunakan Metode Key Performance Indicator (KPI) Pada PT Dua Daya Sakti - Indahyati, Iin; Sunarto, Dewiyani; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT Dua Daya Sakti performs manual performance assessments, there by making the assessment process often stalled even not running. The method used in the assessment previously applied is the Key Performance Indicators (KPI). So the impact that occurs when the assessment of performance at PT Dua Daya Sakti stalled is the HRD and the leadership difficulty in determining the employees who are eligible to get bonuses in accordance with employee performance targets, managers at the company difficulties in evaluating the assessment with the criteria set by the company and measuring the increase and decrease assessment progress performance system. With the problems and impact on PT Dua Daya Sakti, the solution and the conclusion of the problem is the need for performance appraisal application that can assist the company by using the method ever applied by PT Dua Daya Sakti namely Key Performance Indicator (KPI)method. The result of the research and evaluation have shown that the application can assist PT Dua Daya Sakti in performing systematic performance assessment and report required by the company that is report : Performance Appraisal, Employee Bonus Report, Division Evaluation Report and Employee Development Report.